2023
DOI: 10.1039/d3gc00344b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical dual α,β-C(sp3)–H functionalization of cyclic N-aryl amines

Abstract: Herein, a straightforward and efficient route for the construction of dual α,β-C(sp3)–H functionalized cyclic N-aryl amines using a combination of electrocatalysis and iron catalysis is disclosed. This approach is achieved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Two weak main peaks labeled as µ 0 and ν 0 and two intense satellite peaks labeled as µ′ and ν′ positioned at 900.7, 882.5, 904.9, and 886.1 eV, respectively, are assigned to Ce 3+ , suggesting that the Ce species in CePO 4 @N‐P‐CNSs existed only as Ce 3+ . [ 57,58 ] The C 1s and N 1s XPS spectra of CePO 4 @N‐P‐CNSs are deconvoluted into five types of carbon species and five types of nitrogen species, respectively, which are the same as those of N‐P‐CNSs (Figures S8a and S8b). However, in contrast with N‐P‐CNSs, two new peaks at ≈129.8 eV and ≈133.6 eV emerge in the P 2p XPS spectrum of CePO 4 @N‐P‐CNSs assigned to P‐Ce and P‐O in PO 4 3− tetrahedral structure, respectively (Figure 2g and Figures S8c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two weak main peaks labeled as µ 0 and ν 0 and two intense satellite peaks labeled as µ′ and ν′ positioned at 900.7, 882.5, 904.9, and 886.1 eV, respectively, are assigned to Ce 3+ , suggesting that the Ce species in CePO 4 @N‐P‐CNSs existed only as Ce 3+ . [ 57,58 ] The C 1s and N 1s XPS spectra of CePO 4 @N‐P‐CNSs are deconvoluted into five types of carbon species and five types of nitrogen species, respectively, which are the same as those of N‐P‐CNSs (Figures S8a and S8b). However, in contrast with N‐P‐CNSs, two new peaks at ≈129.8 eV and ≈133.6 eV emerge in the P 2p XPS spectrum of CePO 4 @N‐P‐CNSs assigned to P‐Ce and P‐O in PO 4 3− tetrahedral structure, respectively (Figure 2g and Figures S8c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast with N‐P‐CNSs, two new peaks at ≈129.8 eV and ≈133.6 eV emerge in the P 2p XPS spectrum of CePO 4 @N‐P‐CNSs assigned to P‐Ce and P‐O in PO 4 3− tetrahedral structure, respectively (Figure 2g and Figures S8c, Supporting Information). [ 57,59 ] Meanwhile, two new peaks appeared in the O1s XPS spectrum of CePO 4 @N‐P‐CNSs at ≈529.3 eV and ≈531.6 eV, which are assigned to lattice oxygen and Ce—O–P, respectively (Figure 2h and Figures S8d, Supporting Information). [ 59–61 ] Overall, as expected, the XPS results clearly demonstrate that the NPs in CePO 4 @N‐P‐CNSs are CePO 4 , which is in harmony with the findings from the previous XRD results (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The PDES increased the adsorption sites of OVA and enhanced multiple interactions between the sorbent and OVA. 211,212 Li et al 213 reported the modification of magnetic titanium dioxide nanoparticles using a deep eutectic solvent consisting of choline chloride (ChCl) and xylitol (Xyl) (Fe 3 O 4 @TiO 2 @[ChCl] [Xyl]) and its application to chymotrypsin (Chy) solid phase extraction (MSPE). There was also a group led by Ni et al 214 who used carbon nanotubes (CNTs) for magnetization and radical polymerization, followed by solid-phase extraction of bovine serum proteins (BSA) using 3-acrylamidopropyltrimethylammonium chloride solution (APTMAC) and xylitol (Xyl) to coat the surface (Fig.…”
Section: Modify Drug Carriersmentioning
confidence: 99%
“…With our continuous interests in sustainable electrochemistry 85 88 , here we report our effort in the development of this metal-free electrochemical dihydroxylation of unactivated alkenes, as a general, direct, and more environmentally friendly approach for the synthesis of aliphatic vicinal diols (Fig. 1B ).…”
Section: Introductionmentioning
confidence: 99%